2012
DOI: 10.1016/j.ijsp.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Pullout of a lumbar plate with varying screw lengths

Abstract: BackgroundScrew length pertains to stability in various orthopedic fixation devices. There is little or no information on the relationship between plate pullout strength and screw length in anterior lumbar interbody fusion (ALIF) plate constructs in the literature. Such a description may prove useful, especially in the treatment of osteoporotic patients where maximizing construct stability is of utmost importance. Our purpose is to describe the influence of screw length on ALIF plate stability in severely and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While screw length proved to be an important consideration, the density of the bone surrogates played an even larger role in some studies [ 23 , 24 ]. Hitchon et al instrumented cadaveric spines with two of either 12, 14, or 16 mm screws.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While screw length proved to be an important consideration, the density of the bone surrogates played an even larger role in some studies [ 23 , 24 ]. Hitchon et al instrumented cadaveric spines with two of either 12, 14, or 16 mm screws.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ]. Palmer et al found that doubling screw length for ALIF plate constructs translated into approximately twice the pullout strength, while doubling the density of the bone surrogate approximately tripled the pullout load [ 24 ]. Our study demonstrated similar results, suggesting that although longer screw length confers significant ALIF stability, patient bone density may be more important in determining failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations